Flip PDF-assisted e-comic: Hydrocarbon learning media innovation to improve high school students' science literacy - Amala, Dianoza Fadhilal; Dwiningsih, Kusumawati (Universitas Islam Negeri Raden Intan Lampung, 2025)
The low level of students' scientific literacy on hydrocarbon material indicates the need for innovative, interactive, and contextual learning media. This study aimed to develop a Flip PDF-assisted e-comic designed to improve high school students' scientific literacy. A Research and Development (R and D) design employing the ADDIE model was implemented, which included expert validation, practicality testing through student questionnaires, and effectiveness testing using a one-group pretest–posttest design. The developed e-comic received a highly valid score from experts, with an average practicality percentage of 82.1%, categorized as very practical. The effectiveness test showed a significant increase in students' scientific literacy with an N-Gain value of 0.74, categorized as high. The Flip PDF-assisted e-comic improved students' literacy in knowledge, context, competence, and attitude aspects. The results imply that the developed e-comic can help students strengthen their understanding of chemistry concepts, enhance their ability to apply science in daily life, and foster the essential skills required to adapt to technological and global challenges in the 21st century. This research has implications for the development of innovative learning media that can improve students' scientific literacy through an interactive and contextual digital approach.